Unravelling the spatio-temporal variation of zooplankton community from the river Matla in the Sundarbans Estuarine System, India - Tanmoy Nandy; Sumit Mandal (Oceanologia, 2020)
Summary: Zooplankton is an important bioindicator of ecosystem functioning. Knowledge of the seasonal fluctuation in the zooplankton population in estuarine waters of the Indian Sundarbans is rather limited. In the present study, we analysed the community structure of zooplankton assemblages and their spatio-temporal variations based on different multivariate statistics and indicator value analysis. A total of 56 taxa were identified and the density was primarily dominated by planktonic copepods and few meroplankton communities during four sampling seasons. The most abundant species were: Acartia spinicauda, Acartia sp., Bestiolina similis, Euterpina acutifrons, Labidocera acuta, Paracalanus aculeatus, Paracalanus parvus and Paracalanus indicus. Canonical Correspondence Analysis highlighted that temperature, pH, DO, salinity and nutrients were the prevailing environmental parameters associated with significant spatio-temporal changes of zooplankton distribution in this area. The highest abundance of zooplankton was recorded in winter, followed by monsoon, summer and spring. Throughout the study period, different zooplankton indices were observed in good condition. Seasonal occurrence of dominant zooplankton with high IndVal index was markedly observed and it might be used as a potential bioindicator for a particular season and environmental condition in this estuarine complex. The results of this study provide evidence for the presence of warm water species in the estuarine waters of the Indian Sundarbans and can be a clear indication of climate change-mediated elevated temperature in the estuarine system. Our results underscore the high diversity of zooplankton from mangrove dominated estuarine complex and emphasize the need for long-term monitoring in ecologically fragile ecosystems like the Sundarbans Estuarine System.